Fouling behaviour of polyvinylidene fluoride (PVDF) membrane for membrane biological reactor (MBR) application - Lye, Charmaine Jia Mei (Nanyang Technological University, 2022)
Polyvinylidene fluoride (PVDF) material is commonly used to manufacture membranes used in membrane biological reactor (MBR) applications. Due to the nature of the material being hydrophobic, it tends to foul easily in MBR and fouling is considered a major concern for MBR. PVDF membranes are thus usually added with hydrophilic additives to improve the hydrophilicity of the membrane material. A disadvantage of such modification is that hydrophilic additives may leach out over time and be degenerated by chemical cleaning. The hydrophilic properties from the additive will be lost, resulting in changes to the membrane characteristics. Sodium hypochlorite (NaOCl) a common cleaning chemical used in MBR cleaning has not been studied widely for its ageing impact on PVDF membranes. It is known to remove the hydrophilic additives in the membrane due to long term exposure but the fouling behaviour in MBR after ageing is limited. Additionally, PVDF reinforced hollow fiber membranes are seldom studied in literature. This study aims to investigate the fouling behaviour of PVDF reinforced hollow fiber membranes after NaOCl ageing.